Aging and wisdom: age-related changes in economic and social decision making - Lim, Kenneth Teck Kiat; Yu, Rongjun (Frontiers in Aging Neuroscience, 2015)
World life expectancy is increasing and many populations will begin to age rapidly. The impeding prevalence of a greater number of older people living longer lives will have significant social and economic implications. It is important to understand how older people make economic and social decisions. Aging can be associated with a ‘phenomenon of decline’ and also greater wisdom. This paper seeks to examine the relationship between wisdom and aging. It reviews and connects the behavioral sciences and neuroscience literature on age differences in the following social and economic decision making domains that represent subcomponents of wisdom: 1) prosocial behavior in experimental economic games and competitive situations, 2) resolving social conflicts, 3) emotional homeostasis, 4) self-reflection, 5) dealing effectively with uncertainty in the domains of risk, ambiguity and intertemporal choice. Overall, we find a lack of research into how older people make economic and social decisions. There is, however, some evidence that older adults outperform young adults on certain subcomponents of wisdom, but the exact relationship between old age and each subcomponent remains unclear. A better understanding of these relationships holds the potential to alleviate a wide range of mental health problems, and has broad implications for social policies aimed at the elderly.